Polymyalgia Rheumatica and Giant Cell Arteritis - Rovensk<U+00fd>, Jozef.; Leeb, Burkhard F.; Bird, Howard.; `tvrtinov,̀ Viera.; Imrich, Richard. (Springer Vienna, 2010)
This monograph offers current insights into polymalgia rheumatica and giant cell arteritis. Both diseases are typical for advanced age and their incidences increase with aging. Early diagnosis and rapid treatment can save one of the most precious senses - our vision. This book provides an overview on the pathophysiology, their genetic, immunologic, endocrinologic mechanism of these diseases, but most important it deals with state-of-the-art diagnosis and current treatment in elderly with the attempt to diagnose and treat these rheumatic diseases even faster and more effectively in the future.